Micro Credit from Zakah Fund in Baitul Mal Aceh : An Analysis from Law - Adnan, Nurul Ilyana Muhd; Adnan, Hafizuddin Muhd; Adnan, Nurul Izwah Muhd (The journal of contemporary issues in business and government, 2021)
The purpose of this article is to analyze the theoretical distribution of zakah funds to zakah recipients in form of micro credit. The micro-credit zakah distribution is the act of distributing zakah to the asnaf in the form of capital financing. The micro-credit zakah is given to asnaf who want to start a new business or to expand their business. It is questionnable, is there any provision of law that allows zakah to be distributed in the form of micro credit in Baitul Mal Aceh? Based on the findings in the analysis show that the Provision of Indonesian Law No. 38 Year 1999 regarding Zakah Management is not used in Aceh. This is because Aceh government has its own autonomous power. Despite that,there is a Law No. 44 Year 1999,which is the enforcement of law to give a Special Privileges of Aceh Province. Aceh is given the privilege to implement Islamic law in the life of its Muslim people, including issues of zakah distribution.